Antivenom against Crotalus durissus terrificus venom: Immunochemical reactivity and experimental neutralizing capacity - Baudou, Federico Gastón (2017)
The venom of Crotalus durissus terrificus produces a neurotoxic and myotoxic syndrome that can lead to the death. Specific antivenom is the only treatment to neutralize the toxicity of the venom and the precocity in applying the antivenom is crucial for the efficiency of the treatment. We studied the variation of the immunochemical reactivity and neutralizing capacity of the specific antivenom on this venom in pre-incubation and rescue experiments, at different times. ELISA titers increased with longer venom-antivenom incubation times (p < 0.05) nevertheless incubation times had no effect on the neutralizing capacity of the antivenom. The antivenom dose necessary to rescue mice injected with 1.5 MMD (minimal mortal dose) 30 min after venom inoculation was over ten folds the dose of antivenom theoretically required to neutralize the same dose of venom according values obtained from pre-incubation experiments. Results showed that the in vitro immunochemical reactivity is not directly related to the neutralizing capacity. These observations underline the need for a rapid antivenom administration. Although preincubation experiments in mice are a powerful tool for the validation of the potency of the antivenoms in the productive process, it is clear that the nominal neutralization of the antivenoms must not be considered as a “stoichiometric” value regarding the venom to be neutralized in case of natural envenomation and emphasize the need of realization of clinical trials in order to evaluate the adequate doses of antivenom to be therapeutically used.